2023
DOI: 10.1159/000531567
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Attenuates Cerebral Ischemia/Reperfusion Injury through Inducing Autophagy

Abstract: Introduction: The aim of this study was to investigate how melatonin administration for 3 days or 7 days following cerebral ischemia injury (CI/R) would affect autophagy, and therefore, survival in neurons of the penumbra region. Moreover, it was also aimed to determine how this melatonin treatment would affect the neurological deficit score and rotarod and adhesive removal test durations. Methods: Focal CI (90 min) was achieved in a total of 105 rats utilizing a middle cerebral artery occlusion model. After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Beclin-1 is regarded as a major regulator of autophagy, which playing a fatal role in human neurodegenerative diseases, including cerebral ischemia (Mo et al 2020 ; Xu and Qin 2019 ). Increasing evidence showed that autophagy can be evaluated by detecting Beclin-1, LC3 and p62 expression (Yang et al 2021a , b ; Yilmaz et al 2023 ). According to our results, CAT treatment alleviated neuronal injury, decreased MCAO or OGD/R-induced Beclin-1 expression and LC3II/I ratio, and increased p62 level, while Beclin-1 overexpression nullified the protection of CAT in OGD/R-induced RN-c cells.…”
Section: Discussionmentioning
confidence: 99%
“…Beclin-1 is regarded as a major regulator of autophagy, which playing a fatal role in human neurodegenerative diseases, including cerebral ischemia (Mo et al 2020 ; Xu and Qin 2019 ). Increasing evidence showed that autophagy can be evaluated by detecting Beclin-1, LC3 and p62 expression (Yang et al 2021a , b ; Yilmaz et al 2023 ). According to our results, CAT treatment alleviated neuronal injury, decreased MCAO or OGD/R-induced Beclin-1 expression and LC3II/I ratio, and increased p62 level, while Beclin-1 overexpression nullified the protection of CAT in OGD/R-induced RN-c cells.…”
Section: Discussionmentioning
confidence: 99%
“…Protein bands were calculated with GeneTools software (Version 4.03.05, Sygene, Cambridge, UK). 22 , 30 Finally, to include representative Western blot images of the groups in the article, one rat brain tissue from each group was selected and run in gel for Beclin‐1, LC3, p62, caspase‐3 and β‐actin genes. Therefore, in the article, there is the same β‐actin gel image below the gel images of Beclin‐1, LC3, p62 and caspase‐3 genes.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that melatonin inhibits Aβ-induced oxidative stress and cell death in neuronal cells [31][32][33]. Melatonin, a versatile compound, has exhibited neuroprotective effects in both in vitro and in vivo cerebral ischemia/reperfusion (I/R) models [34]. Our previous study showed that melatonin could reduce BACE1 expression in SH-SY5Y cells under normoxic conditions [35].…”
Section: Introductionmentioning
confidence: 99%